2022
DOI: 10.5101/nbe.v14i3.p263-271
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Effect of Using Ultrasound Vibration on the Reproduction of Detail and Surface Hardness of Dental Stone Models

Abstract: Background:The accuracy of surface production details in the dental models determines the success of the dental prosthesis in clinical application. Aim: This in vitro study aims to compare between dental stone models produced using two types of techniques for pouring the addition silicone impression. Method: The control group was poured using the conventional vibration technique at a vibration frequency of 3000 cycles/min and the experimental group was poured by an ultrasound vibration technique at a frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…La estabilidad dimensional es un factor clave para producir prótesis dentales bien ajustadas con propiedades funcionales y estéticas óptimas 25 . Los resultados de los yesos analizados mostraron (después de 2h) que el Elite Rock (0.697%) y el Fuji Rock (0.749%), cumplieron con los estándares que establece la ADA que es de 0 a 0.10% 10 .…”
Section: Discussionunclassified
“…La estabilidad dimensional es un factor clave para producir prótesis dentales bien ajustadas con propiedades funcionales y estéticas óptimas 25 . Los resultados de los yesos analizados mostraron (después de 2h) que el Elite Rock (0.697%) y el Fuji Rock (0.749%), cumplieron con los estándares que establece la ADA que es de 0 a 0.10% 10 .…”
Section: Discussionunclassified
“…Numerous studies have been conducted to use alternative CaCO 3 and CaO sources from the shells of various oyster species, such as C. Cucullata [7], C. Madrasensis [8], and C. Gigas [9]. A literature survey revealed that these calcium-based compounds are used as biomaterial, hydroxyapatite [10][11][12][13], standard Chinese national (CNS 14995) bricks [14], lightweight aggregates [15], cement [16][17][18], and to produce bioglass and calcium aluminoborate glass [19]. However, limited studies have been conducted on waste oyster shells in Malaysia, specifically using local C. Belcheri originating from the Muar River.…”
Section: Introductionmentioning
confidence: 99%